1987
DOI: 10.1161/01.hyp.9.6.561
|View full text |Cite
|
Sign up to set email alerts
|

The opioid peptides. A role in hypertension?

Abstract: SUMMARY This review is an attempt to highlight evidence that may implicate the endogenous opioid system in the pathogenesis of hypertension in humans. The evidence raised includes biochemical, physiological, pharmacological, and behavioral studies conducted in in vitro and in vivo systems, experimental models of hypertension, and humans with essential hypertension. While the compelling biochemical and pharmacological evidence in experimental animals clearly shows the presence of opioid peptides and their recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…There is accumulating evidence to suggest a role for endogenous opioid peptides in central cardiovascular control (Holaday, 1983;Feuerstein, 1985;Feuerstein & Siren, 1987;Siren & Feuerstein, 1992). Mainly, opioid peptides and opiate receptors have been found in specific brain nuclei, with an established role in the regulation of cardiovascular activities (Atweh & Kuhar, 1977;Hokfelt et al, 1977;Fallon & Leslie, 1986;Mansour et al, 1988;Desjardins et al, 1990), and potent cardiovascular effects have been reported following central administration of opioid peptides (Hassen et al, 1983;Pfeiffer et al, 1983a,b;Appel et al, 1986;Kiritsy-Roy et al, 1986;Marson et al, 1989a,b;May et al, 1989;Siren et al, 1989;Jin & Rockhold, 1991;Siren & Feuerstein, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating evidence to suggest a role for endogenous opioid peptides in central cardiovascular control (Holaday, 1983;Feuerstein, 1985;Feuerstein & Siren, 1987;Siren & Feuerstein, 1992). Mainly, opioid peptides and opiate receptors have been found in specific brain nuclei, with an established role in the regulation of cardiovascular activities (Atweh & Kuhar, 1977;Hokfelt et al, 1977;Fallon & Leslie, 1986;Mansour et al, 1988;Desjardins et al, 1990), and potent cardiovascular effects have been reported following central administration of opioid peptides (Hassen et al, 1983;Pfeiffer et al, 1983a,b;Appel et al, 1986;Kiritsy-Roy et al, 1986;Marson et al, 1989a,b;May et al, 1989;Siren et al, 1989;Jin & Rockhold, 1991;Siren & Feuerstein, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…22 Moreover, the renal and mesenteric vasoconstrictions produced by intracerebroventricular DAGO were found to be significantly enhanced in SHR compared with WKY rats. 21 It is of some interest that the regional hemodynamic alterations produced by intracerebroventricular DAGO are similar to those produced by electrical stimulation of the PVH. 10 In light of the facts that microinjection of either DAGO 19 or /3-endorphin into the PVH produced pressor and tachycardiac responses and stimulated sympathoadrenal outflow, the PVH may be considered as one of the sites of action of enkephalins administered intracerebroventricularly.…”
Section: Discussionmentioning
confidence: 99%
“…19 Therefore, /3-endorphin in the PVH has been hypothesized to be involved in the integrative function of the PVH through regulation of sympathoadrenal function in association with feeding. Both the PVH 20 and central opioid systems 21 have been shown to be involved in the development of hypertension in spontaneously hypertensive rats (SHR). For example, ablation of the PVH delayed the development of hypertension in SHR.…”
mentioning
confidence: 99%
“…In general, JL-selective opiates when administered centrally in the rat induce a dose-related pressor response that is accompanied by a biphasic heart rate response (4,5,13,14). It is our view that in the central nervaus system selective activation of the JL-Opioid receptor produces cardiovascular responses in conscious animals through activation of the sympathoadrenomedullary axis.…”
Section: Cardiovascular Effects Of #L-selective Opioidsmentioning
confidence: 99%
“…The endogenaus opioid system consists of a large family of opiatelike peptides: the enkephalins derived from preproenkephalin A, the endorphins derived from preproopiomelanocortin, and dynorphins derived from preproenkephalin B (8 5 ]enkephalin), K (ketocyclazocine), l (ß-endorphin), and (J (SKF-10,047) has been weil established, and the existence of multiple receptor subtypes has been proposed for !l-and K-receptors based on pharmacological and biochemical studies (8,10,12).…”
Section: Introductionmentioning
confidence: 99%